OPTIMAL INTERVAL TIME FOR PREVENTIVE REPLACEMENT DURING DELAY TIME TAKING INTO ACCOUNT MACHINE LOAD - FERRO FERDINANT (NIM : 23405048); Dosen Pembimbing : Prof. Dr. Ir. Bermawi P. Iskandar, PUTRO
The purpose of this research is to detemine optimal interval time for preventive replacement during delay time taking into account machine load. The machine load influences reliability of a machine and the reliability of the machine will degrade when it is operated above the normal load. Failure phase normally starts with the appearance of a fault indication up to failure or breakdown. The interval time between a fault indication up to failure time is called delay time. Deterioration of a machine considering a load factor is modelled using (Accelerated Failure Time) AFT model. This research deals with the determination optimal interval time for preventive replacement during delay time based on AFT model. Two policies is considered, there are Age Replacement during Delay Time Policy (ARDTP) and Opportunistic Age Replacement during Delay Time Policy (OARDTP). Optimal interval time for each policies is obtained by minimizing total cost per time unit. Numerical example is presented to illustrate optimal solutions for normal usage rate and heavy usage rate. Age replacement during delay time policy gives an interval preventive replacement time 42% longer that of opportunistic age replacement during delay time policy and the total cost per time unit for ARDTP is slightly lower that of OARDTP.